Physician Staffing of Slovakia's Healthcare System in the Context of Physicians’ Emigration - Magdalena TUPA; Sergej VOJTOVIC (Communications of International Proceedings, 2020)
The trend of physicians moving abroad for more favorable conditions of employment is significantly increasing. These physicians constitute a group of highly qualified emigrants, motivated by dissatisfaction with working conditions, the state of healthcare in Slovakia, relatively low salaries, and other push factors. Facilities in the country's healthcare system suffer from their shortage, which is reflected in the negative development of several indicators assessing healthcare and the health status of the population. The main aim of the study is to determine the effects of the departure of physicians from Slovakia on the sustainability of the healthcare system in the country. The analysis of the labor market in the sector of healthcare and social assistance, specifically physicians, has been conducted using mathematical-statistical analysis of data obtained from national and international statistical databases. The analysis of the labor market has been carried out using time series. Regression and correlation analyses with statistical significance testing were used to determine the parameters of the regression function. The trend shows a negative development in regards to the state and sustainability of staffing of Slovak healthcare system. The falling number of physicians of productive age is accompanied by the growing number of physician visits, due to the negative demographic development and the stagnating indicator of healthy life expectancy. This increases the demand for healthcare services; the demand which cannot be met in the conditions of the declining number of healthcare professionals due to their emigrating abroad for work.
Keywords: Physicians; Working Conditions; Emigration; Sustainability.